GAYA KEPEMIMPINAN KEPALA SEKOLAH BERBASIS KEARIFAN LOKAL, TELAAH TERHADAP KARAKTERISTIK KEPEMIMPINAN BIMA “MANGGUSU WARU” PADA MADRASAH ALIYAH NEGERI 2 KOTA BIMA - Muhammad Iqbal; Mei Indra Jayanti (Program Studi Pendidikan Biologi STKIP Bima, 2019)
The styles or ways of school principals in encouraging the creation of work discipline, work motivation, and the responsibility of teachers for their work are very diverse, one of which is the leadership style of the manggusu waru based school, this study aims to find out how the characteristics of the manggusu waru leadership style in Madrasah Aliyah Negeri 2 Kota Bima. Descriptive qualitative research methods with interview, observation and documentation data sources. The results of the study showed that the eight characteristics of waru manggusu values were set forth in the school restrat and the standard operating procedures for all school staff were inputed on the values of waru manggusu, so that their characters shaped the personality of employees and teachers in Madrasah Aliyah Negeri 2 Kota Bima.